Maternal adropin levels in patients with gestational diabetes mellitus: a systematic review and meta-analysis. (1st February 2022) - Vivek, Kumar; Reddy, E. Prabhakar; Thangappazham, Balachandar; Raj, Hemanth; Pérez-López, Faustino R.; Varikasuvu, Seshadri Reddy
Abstract: Background: Adropin is a regulatory protein with potential implications in energy homeostasis, glucose regulation, and insulin resistance. Aim: The aim of this meta-analysis was to compare the maternal serum/plasma adropin levels between gestational diabetes mellitus (GDM) patients and non-GDM controls. Methods: Relevant studies were retrieved by online database and manual searching. The standardized mean differences (SMDs) with 95% confidence intervals (CIs) were obtained by a random-effects meta-analysis. A one-study leave-out sensitivity analysis and trimester-wise subgroup analysis were performed. Results: A total of eight observations were included in this meta-analysis. The results based on random-effects meta-analysis indicated that adropin levels were significantly increased in GDM patients as compared to non-GDM controls (SMD = 2.41, 95% CI = 0.52–4.29, p = .01). The sensitivity analysis indicated that no single study had significantly influenced the overall outcome. Conclusions: The results indicate that maternal serum/plasma adropin concentrations were significantly higher in GDM patients as compared to non-GDM controls suggesting the potential associations of adropin in GDM. Despite this, further studies are needed to investigate the mechanistic, diagnostic and prognostic roles of trimester-wise adropin levels in GDM and associated fetal outcomes.